1984
DOI: 10.1093/nar/12.13.5405
|View full text |Cite
|
Sign up to set email alerts
|

RNA polymerase activity and template activity of chromatin after butyrate induced hyperacetylation of histones inPhysarum

Abstract: We have studied the effect of sodium-n-butyrate on endogenous RNA polymerase in Physarum polycephalum.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
9
0

Year Published

1987
1987
1997
1997

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 48 publications
3
9
0
Order By: Relevance
“…We have previously demonstrated that there is no unique correlation between the steady state level of H4 acetylation and transcription during the cell cycle (7). Furthermore we did not observe a difference in the template activity of chromatin for in vitro transcription, when we compared normal Physarum chromatin with chromatin hyperacetylated by butyrate in vivo (8).…”
Section: Introductionmentioning
confidence: 62%
See 1 more Smart Citation
“…We have previously demonstrated that there is no unique correlation between the steady state level of H4 acetylation and transcription during the cell cycle (7). Furthermore we did not observe a difference in the template activity of chromatin for in vitro transcription, when we compared normal Physarum chromatin with chromatin hyperacetylated by butyrate in vivo (8).…”
Section: Introductionmentioning
confidence: 62%
“…Thus, protamine is able to displace core histones from DNA better in S-chromatin as compared to G2-chromatin. To explore whether a specifically elevated acetylation state (as represented by the S-phase chromatin) is responsible for a facilitated histone release or just an unspecific elevation of the acetylation state, as observed after butyrate-induced hyperacetylation (7,8), we compared control chromatin with chromatin from butyrate-treated plasmodia. Butyrate-S-chromatin differs strikingly from control-S-chromatin.…”
Section: Resultsmentioning
confidence: 99%
“…Previous work from our laboratory has shown a lack of correlation between histone acetylation and the transcriptional activity of chromatin in Physarum [2,3]. Recent results on the functional role of histone acetylation suggest that it serves as a general mechanism in the displacement of histones during structural transitions of chromatin [4].…”
Section: Introductionmentioning
confidence: 89%
“…Histones, the main structural proteins of eucaryotic chromatin, undergo various reversible, postsynthetic modifications, among which acetylation of e-amino groups of lysine residues has been extensively studied [1]. Previous work from our laboratory has shown a lack of correlation between histone acetylation and the transcriptional activity of chromatin in Physarum [2,3]. Recent results on the functional role of histone acetylation suggest that it serves as a general mechanism in the displacement of histones during structural transitions of chromatin [4].…”
Section: Introductionmentioning
confidence: 99%
“…This toxic substance might inhibit growth by inhibition of acetyl-CoA synthesis (La Rossa et al 1987) or by a subsequent building up of ␣-amino-n-butyrate, another toxic BAA intermediate (Rhodes et al 1987). There is evidence that ␣-amino-nbutyrate can inhibit cell division in Allium root tips (Langzagorta et al 1988), acetylate histones in Physarum (Loidl et al 1984), and stop cell division in Hordeum roots tips by acidifying the cytoplasm (Reid et al 1985).…”
mentioning
confidence: 99%